Characterization of Datuk Maringgih In the Script Siti Nurbaya: Wajah Di Sebalik Punggung Written by Edy Suisno - Ardafi, Yudhistino; Barkah, Hendri Jihadul; Susanti, Desi (Creativity And Research Theatre Journal, 2024)
Siti Nurbaya: Wajah di Sebalik Punggung, written by Edy Suisno, focuses on the character Datuk Maringgih. In the novel Siti Nurbaya by Marah Roesli, Datuk Maringgih is known as a cruel and greedy man. Datuk Maringgih is a rich old merchant who is considered evil because he married Siti Nurbaya as a debt to all of Siti Nurbaya's family debts. At first glance, Datuak Maringgih's actions look evil and detrimental to Siti Nurbaya. If you pay closer attention, taking into account the traditional aspects regarding the role of the Niniak Mamak in Minangkabau, as stated in the saying "anak dipangku, kamanakan dibimbiang", that a mamak has obligations and takes part in the life of his nephew. Analyze Datuk Maringgih's characterization, and look at three aspects of Lajos Egri, namely physiological, sociological, and psychological. The performance of the script Siti Nurbaya: The Face Behind the Back is realized in the form of a musical drama. According to Joe Deer, a musical drama is a drama performance where the actors who act as characters on stage are required to be able to depict the atmosphere of the story being played using singing and dancing as a medium of expression. A good actor is not only an actor who is good at acting on stage but also has to be proficient with matters related to musicality and choreography. It is not an easy matter to bring a character to life on stage as a musical drama actor. The actor is not only required to act when the performance starts until it ends but also has to master the acting and choreography related to the storyline at the same time.